A criterion of weak compactness for operators on subspaces of Orlicz spaces - Pascal Lefèvre; Daniel Li; Hervé Queffélec; Luis Rodríguez-Piazza (Journal of Function Spaces and Applications)
We give a criterion of weak compactness for the operators on the Morse-Transue space MΨ, the subspace of the Orlicz space LΨ generated by L∞.